SAT0555 MUSCULOSKELETAL ULTRASOUND IN MONITORING RESPONSE TO JAKi IN RHEUMATOID ARTHRITIS PATIENTS: RESULTS FROM A LONGITUDINAL STUDY. (2nd June 2020) - Cipriano, E.; Ceccarelli, F.; Spinelli, F. R.; Garufi, C.; Duca, I.; Mancuso, S.; Alessandri, C.; DI Franco, M.; Priori, R.; Riccieri, V.; Scrivo, R.; Perricone, C.; et al.
Abstract : Background: Therapeutic approach of rheumatoid arthritis (RA) patients has been enriched by the introduction of small molecules. In particular Jak inhibitors (JAKi), baricitinib and tofacitinib, demonstrated their efficacy in patients naïve or resistant to biological treatments in randomized controlled trials. Moreover, these drugs seem to be able to prevent radiographic progression. To date few data are available from the real life context. Ultrasonographic (US) assessment has became a valid imaging tool in the management of RA patients in clinical practice, allowing the evaluation of joint inflammatory status. Together with clinimetric assessment, US could provide a comprehensive assessment of drug response. Objectives: In the present study we aimed at assessing the early response to JAKi treatment by using musculoskeletal US. Methods: In this prospective longitudinal study, we collected data about all consecutive active RA patients starting treatment with JAKi. RA was diagnosed according to the 2010 ACR/EULAR criteria. At each visit, clinical and laboratory data were collected in a standardized and computerized form, including demographics, past medical history, co-morbidities, previous and concomitant treatments. According with study protocol, all patients underwent clinical and US assessment at the following time-points: baseline (T0), 4 weeks (T1) and 12 weeks (T2). Clinical evaluation included tender and swollen joint counts (0-28), patients global health assessment. C-reactive protein (CRP) levels were registered and disease activity was calculated by disease activity score (DAS) in 28 joints by using CRP (DAS28-CRP). A systematic multiplanar grey-scale and power Doppler (pD) US examination was performed by using MyLab Eight Exp Machine (Esaote, Florence, Italy) at level of 22 joints (bilateral I-V metacarpophalangeal, I-V proximal interphalangeal, wrist). According with OMERACT definitions (1) we assessed the presence of synovial effusion, hypertrophy and pD, that were scored according to a semi-quantitative scale (0-3). A total US inflammatory score (0-198) was obtained by their sum. Results: We enrolled 91 patients [F/M 77/14; median age 60.0 years (IQR 15.5); median disease duration 144 months (IQR 126)]. Of these patients, 54 (59.3%) were treated by baricitinib and the remaining 37 by tofacitinib. At baseline we found a median US inflammatory score of 20 (IQR 18.7) and a median DAS28-CRP of 5.0 (IQR 1.56). US assessment demonstrated significant reduction in the median values of inflammatory score already at T1 [median 13 (IQR 14.7), p<0.0001], that was maintained at T2 [median 10 (IQR 11), p<0.0001]. These results are represented in figure 1 . Similar to US inflammatory score, a significant reduction was registered for DAS28-CRP median values [T1 3.5 (IQR 1.73), p<0.0001; T2 3.3 (IQR 1.8), p<0.0001]. No significant differences were found when subgrouping patients according with different JAKi drug, in terms US and clinimetric assessment. Conclusion: In the present study, specifically designed to evaluate the US-detected efficacy of JAKi in RA patients, we demonstrated in a real life setting a significant, early and sustained improvement of inflammatory joint status. References: [1]Wakefield et al, J Rheumatol 2005 Disclosure of Interests: enrica cipriano: None declared, Fulvia Ceccarelli: None declared, Francesca Romana Spinelli Grant/research support from: Pfizer, Consultant of: Novartis, Gilead, Lilly, Sanofi, Celgene, Speakers bureau: Lilly, Cristina Garufi: None declared, Ilaria Duca: None declared, Silvia Mancuso: None declared, cristiano alessandri Grant/research support from: Pfizer, Manuela Di Franco: None declared, Roberta Priori: None declared, Valeria Riccieri: None declared, Rossana Scrivo: None declared, Carlo Perricone: None declared, Guido Valesini: None declared, fabrizio conti Speakers bureau: BMS, Lilly, Abbvie, Pfizer, Sanofi